2020
DOI: 10.3390/biom10020196
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Hydrogen Bonds for the Histamine H2 Receptor-Ligand Interactions: A Lesson from Deuteration

Abstract: We used a combination of density functional theory (DFT) calculations and the implicit quantization of the acidic N–H and O–H bonds to assess the effect of deuteration on the binding of agonists (2-methylhistamine and 4-methylhistamine) and antagonists (cimetidine and famotidine) to the histamine H2 receptor. The results show that deuteration significantly increases the affinity for 4-methylhistamine and reduces it for 2-methylhistamine, while leaving it unchanged for both antagonists, which is found in excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 57 publications
2
17
0
Order By: Relevance
“…Yet, in this case, we are concerned with multiple hydrogen bonds that determine both the hydration and the interaction with the receptor, and since the overall effect (∆∆E BIND ) is a difference between these two quantities, it can, at the end, be either positive or negative, depending on the ligand. In line with that, our earlier report on the same receptor showed that deuteration increased the binding of 4-methylhistamine and gave a reduced affinity for 2-methylhistamine, while offered no change for antagonists cimetidine and famotidine [26]. With this in mind, we have extracted the relevant snapshots from the MD simulation in water and H 2 receptor, both with and without histamine, and truncated the geometries to clusters involving 36 molecules of water, and receptor residues 98-103, 186-190 and 250-254, respectively.…”
Section: Quantum-chemical Calculationssupporting
confidence: 85%
See 3 more Smart Citations
“…Yet, in this case, we are concerned with multiple hydrogen bonds that determine both the hydration and the interaction with the receptor, and since the overall effect (∆∆E BIND ) is a difference between these two quantities, it can, at the end, be either positive or negative, depending on the ligand. In line with that, our earlier report on the same receptor showed that deuteration increased the binding of 4-methylhistamine and gave a reduced affinity for 2-methylhistamine, while offered no change for antagonists cimetidine and famotidine [26]. With this in mind, we have extracted the relevant snapshots from the MD simulation in water and H 2 receptor, both with and without histamine, and truncated the geometries to clusters involving 36 molecules of water, and receptor residues 98-103, 186-190 and 250-254, respectively.…”
Section: Quantum-chemical Calculationssupporting
confidence: 85%
“…The results increase in the histamine affinity, as its pIC50 values (p < 0.05) changed from 7 7.80 ± 0.16 (D2O). Building on that, our subsequent work undertook the same ding of two agonists, 2-methylhistamine and 4-methylhistamine, and two an and famotidine, and showed a notable affinity increase for 4-methylhistam e for 2-methylhistamine, while no change was observed for both antagonists reted in the context of the altered hydrogen bonding strength upon deuterati and interactions with binding sites residues and solvent molecules preceding th t work builds on the mentioned results [25,26], and considers the parent agonist range of computational techniques, involving docking studies, classical simulation, and quantum-chemical calculations within a large cluster model order to offer a more precise insight into the structural and electronic featu and with the aim to provide the molecular interpretation to the observe . The outlined analysis is likely to contribute towards understanding the while the in silico discrimination between agonists and antagonists, based on th With this in mind, instead of utilizing chemical deuteration described earlier, in our preceding work [25], we have taken a different approach of introducing deuteration through the exchange mechanism by performing binding studies in pure D 2 O.…”
Section: 25 X For Peer Reviewmentioning
confidence: 80%
See 2 more Smart Citations
“…Lastly, in order to evaluate a mutual interaction between the QUE and IND themselves in the ternary HSA-IND-QUE complex, a frozen geometry of both ligands, extracted from the representative structure of the complex during MD simulations, was submitted to M06-2X/6-31+G(d,p) calculations. To account for the effect of the enzyme environment, we included the implicit CPCM solvent model, taking the dielectric constant of ε = 4 and all other parameters for pure water, as employed in many of our studies concerning various aspects of biomolecular systems [61,65,66]. The final interaction energy was calculated by comparing the so-obtained energy with energies of individual ligands, again frozen in the geometry they assume in the complex and considering only electronic energy contribution without thermal corrections.…”
Section: Molecular Dynamics Simulations and Quantum Chemical Calculatmentioning
confidence: 99%